PENINGKATAN HASIL BELAJAR TEMAN 1 MUATAN MATEMATIKA MELALUI METODE CURAH PENDAPAT (BRAINSTORMING) PADA SISWA KELAS I SDN 09 TALAWI HILIR - Mariatnita Mariatnita (STKIP Pesisir Selatan, 2019)
Based on the learning outcomes of Class I students at SDN 09 Talawi Hilirit was found that student learning outcomes were still very low. The average student learning outcomes are still below the KKM. The purpose of this study was to describe and obtain information about Improvement of Friends 1 Mathematics subcomputer learning outcomes explain and do the sum of the reduction in the denominator of different denominators and do the multiplication and distribution through Brainstorming Method in Class I SDN 09 Talawi Hilir Sawahunto City. This research is a class action research. Research procedures in this study include planning, action, observation and reflection. This research consisted of two cycles with four meetings. The research subjects consisted of 16 students of Class I SDN 09 Talawi Hilir. Research data were collected using observation sheets and daily tests. Data were analyzed using percentages. Based on the results of the research and discussion that has been stated, it can be concluded that the Brainstorming Method can improve the learning outcomes of Friends 1 The sub mathematics content explains and summarizes the reduction of different denominator fractions and performs the multiplication and division in SDN 09 Talawi Hilir. Student learning outcomes from cycle I to cycle II. Student learning outcomes in the first cycle was 57.85 (enough) increased to 84.77 (good) with an increase of 26.92%.